Investigação in vitro do efeito da restrição proteica no metabolismo do albendazol em ratos e estudos de inibição do crescimento de células tumorais humanas pelos enantiômeros do albendazol sulfóxido - Belaz, Katia Roberta Anacleto (2011)
This work presents an in vitro investigation of protein restriction in the metabolism of albendazole (ABZ). The study was conducted with microsomal fractions obtained from Wistar rats using a High Performance Multidimensional Liquid Chromatography method which was developed and fully validated for the determination of the ABZ metabolites albendazole sulphoxide (ABZ-SO), albendazole sulphone (ABZ-SO2) and albendazole 2-aminesulphone (ABZ-SO2-NH2). The compounds were extracted from the biological matrix using a C8-RAM-BSA column (5.0 x 0.46 cm i.d.) and analyzed on a chromatographic chiral column containing amylose tris(3,5- dimethylphenylcarbamate) (15.0 x 0.46 cm i.d.) with a runtime of 35 min. The results of the biotransformation experiments showed that the protein restriction influenced the oxidative metabolism of ABZ. The production of (+) and (-)-ABZ-SO was higher in the control animals. Aditionally, the production of ABZ-SO enantiomers was enantioselective, where the (-)-ABZ-SO was formed in greater amounts than the (+)- ABZ-SO in control animals. However, this enantioselectivity was not observed when the ABZ biotransformation was conducted with microsomal fractions obtained from protein restriction animals. Four chiral polysaccharide phases were also evaluated for the enantioseparation of ABZ-SO in normal and polar organic elution modes. Among the tested conditions, the tris(3,5-dimethylphenylcarbamate) of amylose and MeOH 100% as mobile phase was selected to perform a semipreparative HPLC separation of ()-ABZ-SO. The pure enantiomers obtained were used in in vitro assays to evaluate the growth inhibitory effects on human tumor cells. Inhibition of cell growth was observed to be more pronounced with the (+)-ABZ-SO compared to (-)-ABZ-SO, particularly in MCF-7 cells where the inhibition was about four times more efficient.